The impact of the organizational climate on school library services A field study of a sample of librarians in the secondary schools of the city of M’sila - Abdelhamid, Belabbas (Journal of Social Sciences and Humanities, 2024)
This study examines the role that the organizational climate can play on school library services in service of the curriculum in order to contribute to the formation of a leading generation imbued with science and knowledge. The researcher reviewed the concept of school libraries and their basic functions, with a focus on school library services for secondary schools of all kinds, both technical and those related to cultural activities. The researcher then presented the concept of the organizational climate as one of the most important factors according to his belief in providing a quality service to students, especially in the secondary education stage. The researcher employed the descriptive analytical approach by adopting a quantitative approach based on the questionnaire tool. Eleven (11) questionnaires were distributed to the librarians responsible for the management of school libraries in the secondary schools in the city of Messila. The aim of the research through the field study was to measure the impact of the organizational climate on the library services provided, and to try to know the opinion of the workers in the prevailing climate in the secondary schools under study to reach the results of the field research. A clear weakness was noted in the services provided by the school libraries in those secondary schools, and it was clearly affected by the prevailing organizational climate in the secondary schools.